THE ADEQUACY OF THE REFLECTION OF THE COMIC BY MEANS OF ANOTHER LANGUAGE: TRANSLATION EQUIVALENCE AND ADEQUACY («СОВРЕМЕННЫЕ ФИЛОЛОГИЧЕСКИЕ ПАРАДИГМЫ: ВЗАИМОДЕЙСТВИЕ ТРАДИЦИЙ И ИННОВАЦИЙ», 2025)
The urgency of the problem is caused by the fact that the issues of adequate reflection in the translation of linguistic means, preservation of the style in translation have always been the most difficult and controversial. It is obvious there is the need to understand as deeply and fully as possible what is common to different people, that is universal human cultural values, to preserve carefully and correctly transmit them while translating from one language to another.The purpose of the article is to compare the translation of the linguistic means of expressing the comic into Russian in short stories (based on the stories of M. Twain, O. Henry, S. Likok). The leading approach to the study of this problem is communicative and practical on the provisions of the theory of translation, which makes it possible to reveal that translation is not a simple modification of some linguistic structures into others, but an important mean of intercultural communication. The main results of the article are that, when considering equivalence, translators often resort to translation at the component and reference levels. The equivalence and adequacy relation is reflected in the paper, five types of equivalence proposed by V.V. Komissarov are examined. Equivalence levels are considered. and three levels of equivalence proposed by Breus E.V. Regularities in language systems that dictate the only contextual possibility of adequate transmission of the content of the text are considered. Materials can be useful in the training of professional specialists in theory and practice of translation, they also consider the problems of translation theory in terms of a comparative analysis of the communicative and pragmatic potential of various languages.
Keywords: Adequate, communicative effect, types of equivalence, levels of equivalence, syntactic semantic pragmatic quivalence, complete partial zero equivalence